Synthesis, crystallization and properties of TeO2/TiO2/B2O3 glasses. (2022) - Iordanova, R.; Bachvarova-Nedelcheva, A.; Peneva, M.
Abstract: This study continues our previous investigations on non-traditional tellurite glasses. Ternary TeO2 /TiO2 /B2 O3 glasses have been obtained applying melt quenching method (up-down) from compositions containing high TeO2 content (60 and 80 mol%). It was established that transparent and brownish coloured homogeneous glasses were obtained. Some physical parameters (density, molar volume, oxygen molar volume and oxygen packing density) were estimated and they gave additional, useful information for the network connectivity. The analysis of IR spectra showed that the glass network consists of TeO4 (tbp), TeO3 (tp), BO3 and BO4 units. The UV–Vis spectroscopy established that glasses containing the highest TeO2 content (80 mol%) and lowest B2 O3 amount (10 mol%) exhibited the lowest cut-off value (368 nm) and highest Eg − 3.37 eV.